2010
DOI: 10.3390/nu2070752
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Absorption of Active Absorbable Algal Calcium (AAACa) and Calcium Carbonate Measured by a Dual Stable-Isotope Method

Abstract: With the use of stable isotopes, this study aimed to compare the bioavailability of active absorbable algal calcium (AAACa), obtained from oyster shell powder heated to a high temperature, with an additional heated seaweed component (Heated Algal Ingredient, HAI), with that of calcium carbonate. In 10 postmenopausal women volunteers aged 59 to 77 years (mean ± S.D., 67 ± 5.3), the fractional calcium absorption of AAACa and CaCO3 was measured by a dual stable isotope method. 44Ca-enriched CaCO3 and AAACa were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We conducted a randomized, open-label, controlled single-center clinical trial to assess the effects of vitamin D3 compounds on osteoporosis. The primary objective was quantitative assessment of intestinal fractional calcium absorption (FCA) using a double isotope method [ 12 14 ]. We compared changes in FCA among patients randomly allocated to receive ELD (0.75 μg/day), ALF (1 μg/day), plain vitamin D3 (800 IU/day), or no vitamin D3 analogue (control).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a randomized, open-label, controlled single-center clinical trial to assess the effects of vitamin D3 compounds on osteoporosis. The primary objective was quantitative assessment of intestinal fractional calcium absorption (FCA) using a double isotope method [ 12 14 ]. We compared changes in FCA among patients randomly allocated to receive ELD (0.75 μg/day), ALF (1 μg/day), plain vitamin D3 (800 IU/day), or no vitamin D3 analogue (control).…”
Section: Methodsmentioning
confidence: 99%
“…However, no data regarding the effect of ELD and ALF on intestinal calcium absorption in humans are available. Therefore, in the present study, we investigated the effect of serum concentration of calcitriol on intestinal calcium absorption in post-menopausal osteoporosis patients using a double isotope method [ 12 14 ]. In addition, we investigated the effects of oral doses of vitamin D3 compounds on intestinal calcium absorption and its effects on other internal organs, such as bone, parathyroid glands, and kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium extracted from marine algae was also found to show a beneficial anabolic effect on bone skeletal calcification in animal models of osteoporosis 38 . Algal calcium prepared from oyster shell powder and seaweed has a higher bioavailability than calcium carbonate 39 .…”
Section: Marine Source Of Calciummentioning
confidence: 98%
“…Calcium absorption has been measured in previous studies using mass balance techniques from an oral calcium source intrinsically labeled with a suitable calcium isotope ( Table 1 ). 6 10 The studies showed that calcium absorbability is as low as 20%–40% after calcium salt administration, 6 11 and many modern diets do not provide the recommended levels of calcium (400–1,200 mg/day). 4 , 8 , 12 Therefore, calcium supplements are recommended for the prevention of calcium-related diseases, and various calcium salts, including calcium carbonate and calcium lactate, have been examined as calcium supplement sources.…”
Section: Introductionmentioning
confidence: 99%